The Experience of Residential Care from the Perspective of Adolescents and Caregivers - Gazilj, Ivana; Borić, Ivana; Ćosić, Andrea (Revija za elementarno izobraževanje, 2021)
Aim of the study is to provide an insight into the experience of residential care from the perspective of beneficiaries and experts. The data was collected in two male residential units. The results show that adolescents and caregivers tend to have a negative attitude toward residential care. Adolescents are even more skeptical about the purpose of treatment since they experience shortcomings in the activities and the methods of treatment, as well as monotony and stigmatization by the local community. Caregivers highlight their disappointment regarding the inadequate intervention system and the complexity of working with children with multiple risks and problems.
Keywords: residential care; experience; adolescents; caregivers